Islamic insurance : a modern approach to Islamic banking - Khorshid, Aly, 1947- (Routledge Islamic studies., 2004)
The book uses relevant Quranic and Sunnah extracts, and the arguments of pro- and anti-insurance jurists to arrive at its conclusion that Muslims can enjoy the peace of mind and equity of an Islamic insurance scheme.